Morphological variations of the shell of the bivalve Lucina pectinata (Gmelin, 1791) - MODESTIN, emma (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
In Martinique, the species Lucina pectinata (Gmelin, 1791) is called "mud clam, white clam or mangrove clam" by bivalve fishermen depending on the harvesting environment. Indeed, the individuals collected have differences as regards the shape and colour of the shell. The hypothesis is that the shape of the shell of L. pectinata (P. pectinatus) shows significant variations from one population to another. This paper intends to verify this hypothesis by means of a simple morphometric study. The comparison of the shape of the shell of individuals from different populations was done based on samples taken at four different sites. The standard measurements (length (L), width or thickness (E - epaisseur) and height (H)) were taken and the morphometric indices (L/H; L/E; E/H) were established. These indices of shape differ significantly among the various populations. This intraspecific polymorphism of the shape of the shell of P. pectinatus could be related to the nature of the sediment (granulometry, density, hardness) and/or the predation. The shells are significantly more elongated in a loose muddy sediment than in a hard muddy sediment or one rich in clay. They are significantly more convex in brackish environments and this is probably due to the presence of more specialised predators or of more muddy sediments.